Zoom Encyclopedia - Mike Goldsmith, Susan Kennedy,Steve Parker,Carole Stott,Isabel Thomas,John Woodward (Dorling Kindersley Ltd, 2011)
Zoom in and zoom out and take in the world from a new perspective. Examine the world from different angles and fresh perspectives in "Zoom Encyclopedia". Captivating and clever, this brand new encylopedia focuses on the world in a unique way. With all subjects interconnected, you can zoom in and zoom out from one page to the next and see how everything is linked. Start your journey underground and watch the plants growing in the soil, then zoom out to a forest scene and meet a deer chewing grass on the forest floor. Imaginative images, close-ups, maps, graphs and infographics will keep you guessing as you move from page to page. You'll Zoom through tricky homework topics in no time with this incredible look-and-learn book.